2021
DOI: 10.1227/ons.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fixation Using the Cortical Bone Trajectory Fixation: A Single Surgeon's Experience With 3-Year Follow-up

Abstract: On the Cover This month's cover highlights the technological innovations of Virtual and Augmented Reality. Operative Neurosurgery actively supports these technologies in our publications through Surgical Videos, interactive 3D figure/models, and supplemental files. These allow our "readers" to participate in surgical rehearsals and training, and enhanced visualization of anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…This step is the key differentiating point compared with previous descriptions of other authors' novel approaches whereby low-profile cages are passed end-on having been preassembled using small endcaps whose sizes are limited by the aforementioned mismatch in insertion corridor and endplate surface area. 18 - 20 A schematic representation of our full technique can be found in Figure 1 . A Video shows an L2 corpectomy.…”
Section: Methodsmentioning
confidence: 99%
“…This step is the key differentiating point compared with previous descriptions of other authors' novel approaches whereby low-profile cages are passed end-on having been preassembled using small endcaps whose sizes are limited by the aforementioned mismatch in insertion corridor and endplate surface area. 18 - 20 A schematic representation of our full technique can be found in Figure 1 . A Video shows an L2 corpectomy.…”
Section: Methodsmentioning
confidence: 99%
“…In 2009, Santoni et al proposed the cortical bone trajectory (CBT), which was designed to increase the contact between the screw and the cortical bone by changing the screw path and improving the stability [ 4 , 5 ]. Recent studies have found that the CBT is more effective than the TT in improving mechanical stability, less intraoperative bleeding, shorter hospital stay, less intrusion of adjacent joints, and less paravertebral muscle damage, Based on these advantages, the CBT technique is no longer limited to osteoporotic patients and has been applied to bariatric patients and revision surgery [ 3 , 6 ]. Authors found that the CBT technique still has shortcomings, the screw track does not utilize the medial and inferior wall of the pedicle and the bone cortex of the lateral edge of the upper endplate, the screw may damage the facet joint and the adjacent intervertebral disc, the screw entry point and the lateral wall of the pedicle were prone to rupture, and the screw entry point lacks reliable anatomical reference structures.…”
Section: Introductionmentioning
confidence: 99%
“…These advantages include smaller incisions and faster operating times, with patient outcomes equivalent to standard pedicle screw use. 1 The prospective study by Arzoglou et al 2 describes 3 years of follow-up for patients who underwent lumbar fixation with CBT screws. Eighty patients with grade 1 spondylolisthesis underwent lumbar fixation by 1 surgeon.…”
mentioning
confidence: 99%
“…Similarly, Wangsawatwong et al 21 demonstrated that cortical screw-rod fixation had different effects on adjacent segment mobility than pedicle screw-rod fixation. Arzoglou et al 2 described 4 patients with adjacent segment disease, 2 of which underwent surgery within 3 years of the index surgery. Future studies are warranted to determine the ideal indications and patient groups suited for CBT fixation and the effects of CBT fixation on adjacent segment disease, radiologic outcomes, and patient-related quality-of-life outcomes.…”
mentioning
confidence: 99%